NANO TECHNOLOGY: ECONOMIC ASPECTS, APPLICATIONS AND RISKS - Budi Santoso; Viktor Vekky Ronald Repi; Harun Umar (Jurnal Ilmu dan Budaya, 2020)
The prospect of nano technology is reviewed. This covers the definitions, historical records, concerns, applications, scope of the future, risks economic aspects, and the need of regulations. From the prospect of economic potentials, it is concluded that Indonesia should take part in developing capabilities in nano technologies. This participation could be initiated by initiating a small study group in UNAS.